Pengaruh Disiplin dan Pelatihan Kerja terhadap Kinerja Karyawan pada Gosha Kitchen and Patisserie Restaurant - Pradnyani, Ni Made Citra; Sadiartha, A.A Ngurah Gede; Susanti, Putu Herny (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The company in its management must be able to organize the human resources in it. The quality of employees will determine the survival of the organization. This study was made to review more deeply the relationship between work discipline and training on employee performance. The study was conducted at Gosha Kitchen and Patisserie Restaurant with a total sample of 85 respondents and was investigated using multiple linear regression analysis techniques. Based on the results of the study, it was found that discipline and training had a significant positive effect on employee performance directly and together. The suggestion in this study is that Gosha Kitchen and Patisserie Restaurant is expected to give a warning or sanction to employees who often come late, motivate employees, so that they are enthusiastic in participating in training and always supervise employees at work and always guide employees, so that later employees are able to work in accordance with predetermined quantity standards.